AUTOMATIC MONITORING AND CONTROLLING SYSTEM USING PLC FOR MUSHROOM PLANT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The white button mushroom is very popular throughout the world and is the most important mushroom of commercial significance in India. It can be successfully cultivated in places where the environmental conditions are favourable but it is cultivated in North India in winter seasons due to the favourable conditions. The optimum temperature for mycelial growth is 22°C- 25°C and that for fruit body formation 14°C -18°C and a high percentage of relative humidity. The mushroom cultivation rooms should have facilities for temperature control and pasteurization processes. The main aim of this paper is to minimize the human care needed for the mushroom plant by automating the mushroom production plant and monitor the crop room environment status. The control system is design with PLC Naxgene 1000 .Temperature transmitter is used to detect the temperature. PID controller valve, sprinkler, 12 volt fan is also installed and turn ON when the temperature is too high design an automated mushroom plant monitoring and controlling system which is purely sensor based and can manage everything with minimal human interference. By using the output signals given by different sensors PLC will maintain the appropriate conditions for the proper growth of plants.